2014
DOI: 10.12659/msm.889891
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 p.R132 mutations may not be actively involved in the carcinogenesis of hepatocellular carcinoma

Abstract: BackgroundRecent studies have identified prevalent isocitrate dehydrogenase 1 (IDH1) codon 132 mutations (p.R132) in gliomas and acute myeloid leukemia (AML). The IDH1 mutations lead to a loss of its normal enzymatic activity and acquisition of neomorphic activity in production of α-ketoglutarate (α-KG) and 2-hydroxyglutarate (2-HG), which finally cause alterations of multiple gene expression of tumorigenesis-associated α-KG-dependent enzymes. The aim of this study was to determine whether IDH1 p.R132 mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…17, 29, 30 HCC harbors no IDH1 mutations, 31 recent studies found IDH2 protein decreased in HCC. 9 Herein, we demonstrated IDH1 and IDH2 had similar RNA expressions in both HCC and peritumoral liver tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17, 29, 30 HCC harbors no IDH1 mutations, 31 recent studies found IDH2 protein decreased in HCC. 9 Herein, we demonstrated IDH1 and IDH2 had similar RNA expressions in both HCC and peritumoral liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Two mechanisms have been reported that dysfunction of IDH and / or TET enzymes, two key factors in 5-hmC generation, that would lead to greatly decreased 5-hmC levels in human tumors: loss-of-function mutations target TET2 and IDH1/2 mutations that result in TET activity inhibition via α -KG reduction and 2-hydroxyglutarate accumulation. 17 , 29 , 30 HCC harbors no IDH1 mutations, 31 recent studies found IDH2 protein decreased in HCC. 9 Herein, we demonstrated IDH1 and IDH2 had similar RNA expressions in both HCC and peritumoral liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…There has been no study of IDH1 mutations in specific subtypes of HCC. HCCs in general showed no remarkable increase of IDH1 mutations [ 4 , 8 , 10 , 11 ]. We performed pyrosequencing for IDH1 mutation analysis in clear cell HCCs and pseudoglandular HCCs.…”
Section: Introductionmentioning
confidence: 99%
“…2-HG also promotes the activity of the Egl nine homolog prolyl-hydroxylases by hypoxia inducible factors [ 42 ]. Similarly, increased 2-HG levels caused by IDH1 mutations activate HIF1α-inducible genes, such as the vascular endothelial growth factor (VEGF) and GLUT-1 [ 43 , 44 ]. IDH1/2 mutations were discovered to occur concomitantly to mutations in TP53 , ATRX , and TERT promoter, to codeletions of 1p/19q, and to molecular alterations in PTEN and EGFR [ 45 , 46 ].…”
Section: Molecular Pathogenesis Of Gbmmentioning
confidence: 99%